(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we initiate the study of a zero forcing hop domination in a graph. We establish some properties of this parameter and we determine its connections with other known parameters in graph theory. Moreover, we obtain some exact values or bounds of the parameter on the generalized graph, some families of graphs, and graphs under some operations via characterizations.